2021
DOI: 10.3390/ma14164684
|View full text |Cite
|
Sign up to set email alerts
|

Study on Storage Stability of Activated Reclaimed Rubber Powder Modified Asphalt

Abstract: The purpose of this research was to make full use of waste lubricating by-products (LBP) and reclaimed rubber powder (RR) to modify asphalt by a one-pot approach, so as to achieve the dual purpose of solving the poor storage stability of reclaimed rubber powder modified asphalt (RRMA) and the realization of solid waste recycling. A variety of characterization techniques were performed to analyze storage stability, conventional properties and microstructure of LBP-activated reclaimed rubber powder modified asph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 33 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Under certain mechanical shearing and thermal oxygen conditions, the stabilizer can generate free radicals, which can crosslink and graft with polymer molecular chains such as SBS, reclaimed rubber powder, and bitumen active functional groups to form grafted copolymers. Thereby, the polymer and bitumen can form a stable spatial structure, finally improve the thermal storage stability of modified bitumen, and solve the segregation of modified bitumen [34]. The technical index test results are shown in Table 6.…”
Section: Methodsmentioning
confidence: 99%
“…Under certain mechanical shearing and thermal oxygen conditions, the stabilizer can generate free radicals, which can crosslink and graft with polymer molecular chains such as SBS, reclaimed rubber powder, and bitumen active functional groups to form grafted copolymers. Thereby, the polymer and bitumen can form a stable spatial structure, finally improve the thermal storage stability of modified bitumen, and solve the segregation of modified bitumen [34]. The technical index test results are shown in Table 6.…”
Section: Methodsmentioning
confidence: 99%
“…To increase the compatibility between CR and asphalt, researchers have made many attempts, , and pretreatment of WCR has been proven to be an effective way. , Pretreatment can remove inert substances from the WCR surface to enhance its surface activity and accelerate the interaction between the WCR and asphalt. Currently, the surface activity of WCR can be increased by thermomechanical, microbiological, and plasma activation methods; the commonly utilized techniques are chemical, mixing oil, and microwave radiation approaches. , These methods are shown in Figure …”
Section: Molecular Dynamics Simulation Of Waste Polymer-modified Asphaltmentioning
confidence: 99%
“…In addition, Liu et al [45] used reactive waste binder particles to enhance the compatibility of PE with asphalt binders, thereby enhancing the storability of the PE-modified asphalt. Kong et al [46] found that waste lubricant byproducts were beneficial to improving the compatibility of recycled binder powder with asphalt and enhancing the storage stability of binder-powdermodified asphalt. Sienkiewicz et al [47] found that the addition of compounds that enable physical and chemical interactions between the modifier and asphalt in modified asphalt can enhance the stability of modified asphalt.…”
Section: Introductionmentioning
confidence: 99%